Discrete automatic schemes for ASC TP (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article given shows functional possibilities of creating discrete automatic schemes in CAD of digital automatic control system (CAD of digital ACS), in complex of Software Design of System of the Digital Control (Complex SDSDC) for automated system of  control of technological processes (ASC TP). Possibilities of complex SDSDC for implementing combination and sequential control compared with requirements of international standard IEC 61131-3:2003 (Part 3: Programming languages) are estimated.